The Effectiveneness Of Using Piaget, Vygotsky, And Brunner Theories In Teaching English For Young Learners At Sdn Kebun Bunga 6 Banjarmasin - Muthmainnah, Inna; Izzatil, Nor; Nor, Hidayah (Tarbiyah : Jurnal Ilmiah Kependidikan, 2019)
To address three theories in teaching English for young learners (Piaget, Vygotsky, and Brunner), the researchers believe that an effective teaching teachniques that pay attention not only to the needs of the young learners but also to their interests are very important. This research reported our pre-experimental study on the effectiveness of using Piaget, Vygotsky, and Brunner theories in teaching English for young learners at SDN Kebun Bunga 6 Banjarmasin. There were 26 students of the fourth grade, study English at SDN Kebun Bunga 6 Banjarmasin, participated in this research. The data collected by conducting three times treatment in one class of the fourth grade, and written tests (pre-test and post-test). Findings revealed that the students got better score after the implementation of those three theories (Piaget, Vygotsky, and Brunner) in the classroom; they were very enthusiastic learned English in the classroom by interacting with the teachers and the peers. Their responses toward this activity were also positive. This research is expected to be beneficial for teachers who are interested in applying those three theories in English classroom, especially for young learners’ classroom.